DEVELOPMENT OF COMMUNICATION IN LATVIAN PUBLIC ADMINISTRATION: TRENDS AND CHALLENGES - Mirlina, Līga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Along with the decrease of administrative influences, the effective functioning of contemporary public administration needs the support and partnership of society. The necessity to consider the reaction of society obliges to inform and to create public understanding on decisions made by the public administration, as well as to ensure an opportunity for individuals to get involved in the decision making process. Thus, the role of communication in public administration performance increases. The regulation of the state needs increasingly greater public acceptance and approval both by responding to the public’s position and wishes and by creating common values and standards that are often achieved by the communication process. In order to understand the role of communications in public administration processes, the author has studied the development of the public administration communication during several state reform stages in Latvia. Using qualitative research methods – interviews, document analysis and comparative analysis and quantitative content analysis –, the trends and challenges in the development of Latvian public administration communication were identified. It is possible to stress two important changes – firstly, the goal of public communications is not just to increase the awareness of the public, but also to involve the public in the state’s development, and secondly, the transformation of communication changes the methods and the way of public administration communication.